2021
DOI: 10.2337/dc20-3092
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Associations of Dietary Glycemic Index, Glycemic Load, and Fiber With 3-Year Weight Loss Maintenance and Glycemic Status in a High-Risk Population: A Secondary Analysis of the Diabetes Prevention Study PREVIEW

Abstract: To examine longitudinal and dose-dependent associations of dietary glycemic index (GI), glycemic load (GL), and fiber with body weight and glycemic status during 3year weight loss maintenance (WLM) in adults at high risk of type 2 diabetes. RESEARCH DESIGN AND METHODSIn this secondary analysis we used pooled data from the PREVention of diabetes through lifestyle Intervention and population studies in Europe and around the World (PREVIEW) randomized controlled trial, which was designed to test the effects of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…PBDs rich in healthy components have higher dietary fiber and micronutrients as well as lower energy, GI, and glycemic load [27]. In a previous secondary analysis of the PREVIEW study, we found positive associations between GI, glycemic load, and weight regain during WLM [34].…”
Section: Discussionmentioning
confidence: 59%
“…PBDs rich in healthy components have higher dietary fiber and micronutrients as well as lower energy, GI, and glycemic load [27]. In a previous secondary analysis of the PREVIEW study, we found positive associations between GI, glycemic load, and weight regain during WLM [34].…”
Section: Discussionmentioning
confidence: 59%
“…Studies on the effect of GI on appetite are equivocal and controversial. A secondary observational analysis of the PREVIEW cohort found that participants in the lowest tertile of GI and glycemic load regained less weight over 3 years than the highest tertile (49). A review of short-term and mediumterm studies (<1-year) found that short studies did not support an acute effect of GI on satiety, whereas the findings of longer studies were mixed (50).…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved at all intervention centres by the local human research ethics committees and was conducted in accordance with the latest revision of the Declaration of Helsinki (59th WMA General Assembly, Seoul, Republic of Korea, October 2008). University of Sydney: HREC approval on 24 The main outcomes of interest were fasting plasma glucose, insulin, and C-peptide concentrations, and glycated hemoglobin A 1c (HbA 1c ) measured at each time point. The secondary outcomes of interest were fat mass, waist circumference, and BMI.…”
Section: Methodsmentioning
confidence: 99%
“…The PREVIEW (PREVention of diabetes through lifestyle Intervention and population studies in Europe and around the World) study was a long-term randomised controlled weight loss maintenance trial designed to test the effects of four diet and physical activity interventions in a 2 × 2 factorial design on the incidence of T2D in individuals with overweight or obesity and pre-diabetes after an initial 8-week weight loss period on a predominately liquid low-energy diet [23]. In post hoc analyses of PREVIEW, dietary GI and GL were positively associated with weight regain and deteriorating glycaemic status [24]. The aim of the present secondary analysis was to investigate longitudinal associations of added, free and total sugars intakes [25], as well as GI as a comparator, with indices of glucose metabolism (IGM) (fasting plasma glucose, insulin, C-peptide and HbA 1c ) and indices of body fat (IBF) (total body fat, waist circumference, and BMI) during a 3-year weight loss maintenance phase in those centres that provided data on added and/or free sugars.…”
Section: Introductionmentioning
confidence: 99%